Mapping Research on Problem-Solving Skills in Physics Education: Bibliometric Analysis - Hermanto, I Made; Maharani, Ni Luh Sri; Nurhayati; Kurniasari, Septiana (Program Studi Tadris IPA, Fakultas Tarbiyah (IAIN) Kediri, Indonesia, 2024)
This research aims to conduct a bibliometric analysis of literature related to problem-solving abilities in the context of physics learning. Through searching and analyzing relevant publications (articles, conference papers, reviews, and book chapters) using the Scopus database, research trends related to this topic were mapped. A total of 192 publications were obtained using Harzing's Publish or Perish application. Bibliometric analysis was carried out in this study. Search results from the Scopus database were extracted using VOSviewer software. The results of the analysis show that although there have been a number of studies conducted, problem-solving abilities in physics learning are still an interesting area for further research. There are great opportunities for further research involving the relationship between problem-solving abilities and various aspects, such as instrument development, STEM approaches, use of augmented reality technology, collaboration in problem solving, ability testing, student self-confidence, and learning materials. These findings show the importance of a deeper understanding of problem-solving abilities in the context of physics learning.